2009
DOI: 10.1111/j.1398-9995.2009.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Under‐report and underdiagnosis of chronic respiratory diseases in an African country

Abstract: Background:  Chronic respiratory diseases (CRD) are greatly underestimated. The aim of this study was to assess the burden associated with reported CRD and chronic obstructive pulmonary disease, as defined on the basis of various standardized criteria, by estimating their point prevalence in a sample of individuals attending the Primary Health Care (PHC) level and Emergency Room (ER) Departments in Cape Verde (CV) archipelago. The second aim of the study was to identify factors related to airways obstruction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Moreover, it is believed that the under-recognition of COPD in African countries may be because patients present late and, even after presentation to health services, diagnoses are typically delayed until the disease is relatively advanced (40,41). Research fi ndings have shown that lack of (use of ) spirometers poses a very important practical challenge in rural settings with the main reasons being due to unavailability, improper usage, and low awareness of their importance (11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, it is believed that the under-recognition of COPD in African countries may be because patients present late and, even after presentation to health services, diagnoses are typically delayed until the disease is relatively advanced (40,41). Research fi ndings have shown that lack of (use of ) spirometers poses a very important practical challenge in rural settings with the main reasons being due to unavailability, improper usage, and low awareness of their importance (11).…”
Section: Discussionmentioning
confidence: 97%
“…In health service delivery, studies have reported that many health workers are ill-equipped in diagnosing COPD, making the under-diagnosis of COPD a problem confronting many African nations (40). Moreover, it is believed that the under-recognition of COPD in African countries may be because patients present late and, even after presentation to health services, diagnoses are typically delayed until the disease is relatively advanced (40,41).…”
Section: Discussionmentioning
confidence: 98%
“…The asthma diagnosis had been based mainly on clinical history, and only 42% of GPs instruct patients to use a peak flow meter to monitor symptoms. Underreporting, underdiagnosis and undertreatment of chronic respiratory diseases is a fact in most parts of the world (10).…”
mentioning
confidence: 99%
“…We found an overall prevalence of 4.5% for chronic bronchitis and 0.7% for emphysema diagnosis. However, under-diagnosis and under-reporting of respiratory diseases exist in Cape Verde, as previously published [12].…”
Section: Discussionmentioning
confidence: 88%
“…This study resulted from an official protocol between the Ministry of Health from Portugal and Cape Verde and was included in the Global Alliance Against Chronic Respiratory Diseases (GARD) initiative [11], in accordance with the previously published protocol [12].…”
Section: Methodsmentioning
confidence: 99%